STUDENT WORKSHEETS (LKS) AS AN ALTERNATIVE ASSESSMENT FOR BLENDED LEARNING IN ELEMENTARY SCHOOLS - Leni Yuliana; Desi Eka Pratiwi (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
School is one of the manifestations of formal education in which interactions occur between teachers and students in learning activities. The purpose of this study is to describe student-learning activities in using LKS as an alternative assessment in blended learning in elementary schools. This study used descriptive qualitative approach using mixed method technique, which combines quantitative and qualitative analysis. Data calculations were carried out quantitatively and described qualitatively. The data collection technique was observation of student activities. The data analysis technique uses an analysis of the results of the student activity observation sheet through a quantitative descriptive presentation. Based on the details of the percentage for each indicator, it can be seen that the students’ learning activities classically obtain a score percentage of 92.58% in the very high category. Thus, it can be concluded that students’ worksheets (LKS) as an alternative assessment can increase students’ learning activities through blended learning.